DISTORSI MITOS DAN DEKONSTRUKSI IDENTITAS NON-BINER DALAM DESAIN TAS KECIL LE CHIQUITO - Resmisari, Ganis (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
The micro bag Le Chiquito by designer Jacquemus has become a symbol of visual culture that reflects both the distortion of meaning and the deconstruction of non-binary identity in the contemporary fashion landscape. This article analyses the shift in meaning from utilitarian function to status symbol, expression, and representation of identity by employing Barthes' theory of myth and Derrida's deconstructive approach. Le Chiquito emerges as a marker that challenges binary oppositions such as functional vs. nonfunctional and masculine vs. feminine, while also opening a new space for gender expression in consumerist culture. Using a cultural studies approach and semiotic analysis, this study demonstrates that fashion objects have the potential to serve as mediums of ideological discourse in capitalist society, particularly in the digital era.